A Correlation between Students’ Self-Esteem and Speaking Skill - Tiara Tripudiyana; Dewi Sartika; Ratna Nery (Journal of English Language Teaching and Learning (JETLE), 2022)
The aim of learning English was to develop students’ competence in oral and written communication to research the functional literacy stated in the 2013 Curriculum. This study investigated the link between students' self-esteem and their speaking skills. It employed correlational study. A questionnaire and an oral test were employed to collect data. A questionnaire was utilized to assess the students' self-esteem, and an oral test was employed to assess their speaking abilities. The eleventh graders at SMAN 5 Ogan Komering Ilir were the focus of this study. 103 students selected as a sample from a population of 172. A Pearson Product Moment Correlation method was used to examine the data. The study's findings revealed that r-obtained (0.644) was greater than r-table (0.194) when the p-value (0.000) was less than 0.05. It meant that the null hypothesis (Ho) had been rejected and that the alternative hypothesis (Ho) had been accepted. In other words, there was a link between students' self-esteem and their ability to communicate. It is possible that learners' self-esteem influenced their speaking abilities. As a result, the higher the learners' self-esteem, the better their speaking abilities.